Analysis of vertical strip wound fault-tolerant permanent magnet synchronous machines - Arumugam, Puvaneswaran; Hamiti, Tahar; Brunson, C.; Gerada, C. (Institute of Electrical and Electronics Engineers, 2013)
This paper investigates the behavior of a vector- controlled, fault-tolerant, permanent magnet motor drive system adopting a vertically placed strip winding (VSW) which can limit inter-turn short-circuit (SC) fault current to its rated value regardless of the position in the slot containing the shorted turns. The drives’ dynamic behavior is simulated using a per-phase equivalent circuit model with the winding inductances and resistances analytical calculated based on the machine geometry and fault location. A simplified thermal model is also grafted into the system model to effectively simulate the dynamic behavior of the machine during healthy, inter-turn SC fault and post-fault controlled scenarios. The SC fault current limiting capability, the additional losses and thermal behavior of the winding are studied and compared with conventional winding adopting round conductors winding (RCW). The proposed winding design is verified with Finite Element (FE) analysis and then validated experimentally. Results show that the VSW inherently limits the SC current, reduces its dependence on the position of the fault within the slot but results in an increase in AC losses.